Child Poverty in the Philippines - Aubrey D. Tabuga; Celia M. Reyes; Ronina D. Asis; Maria Blesila D. Mondez (Philippine Institute for Development Studies (PIDS), 2014)
Despite the remarkable economic performance of the Philippines in recent years, poverty remains a core policy issue. And with a relatively young population, the poverty situation concerns largely children who are at the critical stages of their physical, mental, and social development. This report provides a comprehensive profile of children who are living in poverty through data collected from national surveys and administrative records of government agencies. The estimations show that in 2009, 13.4 million or over a third of all children aged below 18 are living below the poverty line. Both the incidence and magnitude of poor children are increasing through years. Moreover, around 10 million face at least two overlapping types of severe deprivation in basic amenities while an estimated three quarters of a million face at least five kinds of deprivation simultaneously. Although these children can be found in the different regions of the country, several areas that consistently lag behind in many poverty aspects have been identified. Meanwhile, longitudinal data show that a non-negligible number of families move in and out of poverty and this vulnerability poses risks on children's well-being. With the recent trend in population growth, the lack of inclusivity of economic growth, and the exposure of the country to natural calamities, we would expect that the number of children in dire condition would not be significantly reduced within the next few years.
Keywords: 330; poverty; Philippines; panel data; children; deprivation